2021
DOI: 10.1093/cercor/bhab399
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal whisker-dependent behaviors and altered cortico-hippocampal connectivity in Shank3b−/− mice

Abstract: Abnormal tactile response is an integral feature of Autism Spectrum Disorders (ASDs), and hypo-responsiveness to tactile stimuli is often associated with the severity of ASDs core symptoms. Patients with Phelan-McDermid syndrome (PMS), caused by mutations in the SHANK3 gene, show ASD-like symptoms associated with aberrant tactile responses. The neural underpinnings of these abnormalities are still poorly understood. Here we investigated, in Shank3b−/− adult mice, the neural substrates of whisker-guided behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…It should be noted that a similar upregulation in mRNA expression has been shown in the cerebellum and parietal cortex of individuals with ASD (Fatemi et al, 2014). Upregulation found in GABAergic markers in the trigeminal ganglia can be consequently interpreted as underlining increased inhibition and thus giving way to hyporeactive/hyposensitive behaviors in adult Shank3b -/- and Cntnap2 -/- mice (Balasco et al, 2020; Balasco et al, 2021). In juvenile mice, on the other hand, an upregulation was found among Shank3b -/- TG for Gabrd, a gene whose dysfunction promotes psychomotor delay and epilepsy (Windpassinger et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that a similar upregulation in mRNA expression has been shown in the cerebellum and parietal cortex of individuals with ASD (Fatemi et al, 2014). Upregulation found in GABAergic markers in the trigeminal ganglia can be consequently interpreted as underlining increased inhibition and thus giving way to hyporeactive/hyposensitive behaviors in adult Shank3b -/- and Cntnap2 -/- mice (Balasco et al, 2020; Balasco et al, 2021). In juvenile mice, on the other hand, an upregulation was found among Shank3b -/- TG for Gabrd, a gene whose dysfunction promotes psychomotor delay and epilepsy (Windpassinger et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse lines harboring ASD-relevant mutations have been recently used to assess the neurobiological underpinnings of abnormal sensory responses in ASD within the central and the peripheral nervous system (He et al, 2017;Balasco et al, 2019Balasco et al, , 2020Chelini et al, 2019;Orefice, 2020;Pizzo et al, 2020). Given the relevance of the whisker system in mice, the assessment of TG neurons (which mediate tactile sensitivity from the whiskers) represents a promising tool to study somatosensory processing defects in ASD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse response to the whisker stimulation is then quantified using predetermined behavioral categories (BCs). BCs used thus far aim to deconstruct the animals' response by exploring independent instances of either anxious or explorative behaviors [1][2][3][4] . Previous studies have shown how behavioral abnormalities identified with the WNt are reliably well-matched with similar observation in people with ASD [5][6][7][8] , showing a solid translational validity and opening the possibility of directly investigating the neurobiological underpinning of this common phenotypic trait [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%